Eco-anxiety, climate change and the ‘bottom billion’: a plea for better understanding - Colin David Butler (BMJ Mental Health)
Climate change poses enormous, rapidly increasing risks to human well-being that remain poorly appreciated. The growing understanding of this threat has generated a phenomenon often called ‘eco-anxiety’. Eco-anxiety (and its synonyms) is best documented in the Global North, mostly among people who are better educated and whose reasons for concern are both altruistic and self-interested. However, the populations who are most vulnerable to climate change are disproportionately poor and live in the Global South, where evidence for eco-anxiety (or climate) anxiety is limited, especially among those who have been called the ‘bottom billion’, approximately the global population’s poorest decile. Here, I postulate reasons for this research gap as both ethical and practical. Additionally, the bottom billion experience many disadvantages, some of which plausibly lower their recognition of anthropogenic climate change. These disadvantages include nutritional and health factors that can reduce learning capacity, even if access to formal education exists. Many in this population have limited or no electronic access to information. Furthermore, the relationship between the stresses faced by such populations and climate change is often indirect, potentially also disguising recognition of the role of climate change. The world is characterised by many distressing forms of inequality, one of which is the effective ‘invisibilisation’ of the bottom billion. This group faces many challenges; some of these may exceed climate change as rational causes for anxiety. However, it is here argued that policy makers should act on their behalf, irrespective of evidence that they experience eco-anxiety.